TENSOR FASCIA LATA CROSS THIGH MYOCUTANEOUS FLAP FOR HEEL RESURFACING - RAHUL SAHAI (Indian Journal of Plastic Surgery)
Heel resurfacing by cross thigh Tensor Facia Lata myocutaneous flap successfully performed in three cases of extensive soft tissue defects has been pre rented.